The Level of Dyscalculia in Children with Special Needs in Understanding Mathematical Concepts : Learning Difficulties Experienced - Lutfiyah Lutfiyah; Frida Murtinasari; Dwi Noviani Sulisawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze the difficulties of students with special needs (mentally retarded, deaf, and blind children) in understanding mathematical concepts, which will be described by levels. The research uses descriptive method. Data collection technique used observations of students with special needs to see the difficulties in understanding mathematical concepts (dyscalculia), and interviews conducted with mathematics teachers to complement the results of the observations. The research sample is deaf students, blind students, and mentally retarded students in the Jember district. The data analysis technique in this study uses the flow model. The results of this study were that the level of achievement with good assessment categories was dominated by blind students, namely from 10 aspects of the assessment only weak in the section on grouping the shape dimensions, while the deaf achieved good assessments, namely 1) sorting objects based on the length and short size, 2) understanding the number of objects, 3) understanding numbers, and 4) writing and saying numbers. Meanwhile, mentally retarded students only have 1 good assessment aspect, namely understanding the length of objects. The conclusion is that dyscalculia is mostly suffered by mentally retarded children, deaf children suffered moderate level, and the best level of the subject is blind children.